2000
DOI: 10.1074/jbc.m002358200
|View full text |Cite
|
Sign up to set email alerts
|

Chimeric Melatonin mt1 and Melatonin-related Receptors

Abstract: Melatonin receptors bind and become activated by melatonin. The melatonin-related receptor, despite sharing considerable amino acid sequence identity with melatonin receptors, does not bind melatonin and is currently an orphan G protein-coupled receptor. To investigate the structure and function of both receptors, we engineered a series of 14 chimeric receptor constructs, allowing us to determine the relative contribution of each transmembrane domain to ligand binding and receptor function. Results identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…Mutagenesis studies performed either on the human [14-17] or ovine MT1 receptor [18] and studies using human chimeric GPR50/MT1 receptor constructs [19,20] have shown several highly conserved residues in transmembrane helices that are critical for ligand binding especially those in transmembrane helix III (TMIII: S110, G258) (Fig. 3).…”
Section: Resultsmentioning
confidence: 99%
“…Mutagenesis studies performed either on the human [14-17] or ovine MT1 receptor [18] and studies using human chimeric GPR50/MT1 receptor constructs [19,20] have shown several highly conserved residues in transmembrane helices that are critical for ligand binding especially those in transmembrane helix III (TMIII: S110, G258) (Fig. 3).…”
Section: Resultsmentioning
confidence: 99%
“…The importance of residue 5.43 for ligand binding and receptor stabilization is also sustained by site-directed mutagenesis experiments performed on a number of rhodopsin-like receptors [41,42]. Mutation of Gly258 6.55 to threonine brought to a severe loss of 2-iodomelatonin binding affinity and to a remarkable impairment of signal transduction [43,44]. In most GPCR structures, residue 6.55 is located at the C -terminus of TM6, near the extracellular edge of the helical bundle.…”
Section: Mt1 and Mt2 Melatonin Receptorsmentioning
confidence: 99%
“…Indeed, Val261 6.58 and Pro265 6.62 formed hydrophobic interactions with the alkyl portion of the propionamide group and the amide oxygen and hydrogen atoms interacted with Tyr175 and Ser182, respectively, located on ECL2. Although no mutagenesis data are available for positions 6.58 and 6.62, the importance of the ECL2 portion in ligand binding to the MT 1 receptor has been assessed in studying chimeric melatonin receptors [44]. Ramelteon did not interact with the two serine residues located on TM3, Ser110 3.35 and Ser114 3.39 , which were shown to be fundamental for ligand stabilization.…”
Section: Mt1 and Mt2 Melatonin Receptor Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, it seems that MT 1 selectivity is favored by replacement of the 5-methoxy group with a larger substituent. [31,41,42] Both site-directed mutagenesis experiments [43][44][45][46] and work with chimeric receptors [47,48] have been employed to investigate the structure-function relationships for MT 1 and MT 2 receptors. Unfortunately, no clear information has been obtained about which amino acids are essential for ligand binding, but there is evidence that agonist and antagonist binding sites are not identical.…”
Section: C)mentioning
confidence: 99%